2021
DOI: 10.1177/00220345211026838
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization of Dental Tissues Treated with Silver Diamine Fluoride

Abstract: Silver diamine fluoride (SDF) is a dental biomaterial used to arrest dental caries. To better understand SDF’s mechanism of action, we examined the localization of silver within the tissues of SDF-treated teeth. Carious primary teeth fixed within 2 min of SDF application (SDF-minutes, n = 3), at 3 wk after SDF application in vivo (SDF-weeks, n = 4), and at 2 y after multiple SDF applications in vivo (SDF-multiple, n = 1) were investigated in this study. Carious primary teeth without SDF application (no-SDF, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…However, in the treated regions of the SDF-treated control dental tissue, a significantly greater Ca/P ratio was demonstrated for both SDF-treated enamel and dentin regions, as compared with untreated regions of the same sample and from the untreated control samples. A 2021 study investigated the effects of SDF on carious primary teeth regions and found SDF treatment promoted pathologic mineral by altering physiochemical properties of the tooth structures [ 82 ]. Their detailed results include structural and elemental analysis of SDF-treated teeth which reported EDS results consistent with our findings [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the treated regions of the SDF-treated control dental tissue, a significantly greater Ca/P ratio was demonstrated for both SDF-treated enamel and dentin regions, as compared with untreated regions of the same sample and from the untreated control samples. A 2021 study investigated the effects of SDF on carious primary teeth regions and found SDF treatment promoted pathologic mineral by altering physiochemical properties of the tooth structures [ 82 ]. Their detailed results include structural and elemental analysis of SDF-treated teeth which reported EDS results consistent with our findings [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…A 2021 study investigated the effects of SDF on carious primary teeth regions and found SDF treatment promoted pathologic mineral by altering physiochemical properties of the tooth structures [ 82 ]. Their detailed results include structural and elemental analysis of SDF-treated teeth which reported EDS results consistent with our findings [ 82 ]. The increased Ca/P ratio in the SDF-treated control sample indicates that in these carious lesions of the tooth, the SDF treatment creates a more stable CaP material closer resembling a calcium-deficient apatite [ 44 , 61 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that SDF application increases the radiopacity of the entire carious lesions. This is likely due to the presence of silver ions [ 11 ]. However, other compounds such as Calcium Fluoride (CaF2) could also have formed and contributed to the change in radiopacity of the carious lesion after SDF application [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Securing durable adhesion to tooth surfaces using strategies that modify and/or chemically interact with components in the dentin surface is discussed in 3 articles (Alkattan et al, 2021; Cai et al, 2021; Maravic et al, 2021). Biomineralization mechanisms and arrest of carious lesions are explained (Sulyanto et al, 2021). Mineralization as it relates to regeneration of dentin, as well as pulp regeneration with stem cells and innovative scaffolds, forms the basis of 3 additional articles (Chang, Ma et al, 2021; Soares et al, 2021; Zou et al, 2021).…”
mentioning
confidence: 99%